Customer behavior and decision making in the refurbishment industry‐a data mining approach - Huang, Chung-Fah; Hsueh, Sung-Lin (Journal of Civil Engineering and Management, 2010)
The study of consumer behavior in the refurbishment industry is crucial to the business operation of firms, but there is a lack of research in this regard. With reference to the EKB model specific to consumer behavior, this paper discusses the relationship among consumption characteristics, firm selection behavior and satisfaction degree of refurbishment customers. 242 valid questionnaire copies were collected from refurbishment customers, and analyzed using Decision Tree Analysis and Association Rules in Data Mining. The research results show that, over half of the customers tend to entrust the refurbishment to well‐reputed firms. Moreover, the integrity of refurbishment equipment, response of refurbishment personnel, professionalism and confidence are key elements in service quality (SQ). The best marketing policy for the customers is one which provides more attractive services. These research findings may provide a useful reference for innovative refurbishment firms in their decision‐making.Published Published Online: 14 Oct 2010